Digital communication systems engineering with software-defined radio - Pu, Di; Wyglinski, Alexander M. (Mobile communications series, 2013)
By prototyping and evaluating actual digital communication systems capable of performing "over-the-air" wireless data transmission and reception, this volume helps readers attain a first-hand understanding of critical design trade-offs and issues. It helps professionals gain a sense of the actual "real-world" operational behavior of these systems